Trends and Impact of Door-to-Balloon Time on Clinical Outcomes in Patients Aged <75, 75 to 84, and ≥8585 Years With ST-Elevation Myocardial Infarction - Yudi, M.; Hamilton, G.; Farouque, O.; Andrianopoulos, N.; Duffy, S.; Lefkovits, J.; Brennan, A.; Fernando, D.; Hiew, C.; Freeman, M.; Reid, Christopher; Dakis, R.; et al. (Excerpta Medica, Inc, 2017)
Guidelines strongly recommend patients with ST-elevation myocardial infarction (STEMI) receive timely mechanical reperfusion, defined as door-to-balloon time (DTBT) =90 minutes. The impact of timely reperfusion on clinical outcomes in patients aged 75-84 and =85 years is uncertain. We analysed 2,972 consecutive STEMI patients who underwent primary percutaneous coronary intervention from the Melbourne Interventional Group Registry (2005-2014). Patients aged < 75 years were included in the younger group, those aged 75-84 years were in the elderly group and those =85 years were in the very elderly group. The primary endpoints were 12-month mortality and major adverse cardiovascular events (MACE). 2,307 (77.6%) patients were < 75 years (mean age 59 ± 9 years), 495 (16.7%) were 75-84 years and 170 (5.7%) were =85 years. There has been a significant decrease in DTBT over 10 years in younger and elderly patients (p-for-trend < 0.01 and 0.03) with a trend in the very elderly (p-for-trend 0.08). Compared to younger and elderly patients, the very elderly had higher 12-month mortality (3.6% vs 10.7% vs. 29.4%; p = 0.001) and MACE (10.8% vs 20.6% vs 33.5%; p = 0.001). DTBT =90 minutes was associated with improved outcomes on univariate analysis but was not an independent predictor of improved 12-month mortality (OR 0.84, 95% CI 0.54-1.31) or MACE (OR 0.89, 95% CI 0.67-1.16). In conclusion, over a 10-year period, there was an improvement in DTBT in patients aged < 75 years and 75-84 years however DTBT =90 minutes was not an independent predictor of 12-month outcomes. Thus assessing whether patients aged =85 years are suitable for invasive management does not necessarily translate to worse clinical outcomes.